A Novel N-Type Molecular Dopant With a Closed-Shell Electronic Structure Applicable to the Vacuum-Deposition Process - Matsuo, Takaya (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.